Evaluation of Isoflavone Rich Soy Protein Supplementation for ostmenopausal Therapy - Radhakrishnan, Gita; Rashmi; Agarwal, Neera; Vaid, Neelam B. (Pakistan Journal of Nutrition, 2009)
To examine effects of 6 months supplementation of isoflavone rich soy protein on symptoms, lipid profiles and bone density in postmenopausal women. In this double blind, placebo controlled trial, hundred healthy postmenopausal women not taking Hormone Replacement Therapy, were randomly assigned to consume either 25 g soy protein isolate containing 75 mg isoflavones (study group) or 25 g casein protein (control group) daily. Monthly assessment for acceptability and side effects, 3 monthly for menopausal symptoms (Kupperman Menopausal Index; KMI) and serum lipid-profile, 6 monthly for follicular stimulating hormone, Estradiol levels, vaginal cytology, endometrial thickness and bone density were done. t-test, Analysis of Variance (ANOVA) and chi-square (χ2) tests were employed. Significantly higher number of cases reported improvement in hot-flashes, joint-pains and vaginal-dryness on soy treatment (p<0.05). Soy supplement was significantly superior to placebo in reducing KMI (p<0.05). Soy group showed 7.7% decrease in total cholesterol and 14% decrease in LDL-cholesterol (significantly different from control group p<0.05) while no effect was seen on HDL cholesterol, Blood pressure, sex hormones, vaginal cytology, uterine endometrium and bone densitometry. A 25 g soy supplement containing 75 mg of isoflavones may be an effective alternative therapy for menopausal symptoms and may offer a benefit to cardiovascular-system by altering lipid-profile favorably.